Vasopressin-Independent Regulation of Aquaporin-2 by Tamoxifen in Kidney Collecting Ducts - Tingskov, Stine Julie; Choi, Hyo-Jung; Holst, Mikkel R.; Hu, Shan; Li, Chunling; Wang, Weidong; Frøkiær, Jørgen; Nejsum, Lene N.; Kwon, Tae-Hwan; Nørregaard, Rikke (Frontiers in Physiology, 2019)
Arginine vasopressin (AVP) mediates water reabsorption in the kidney collecting ducts through regulation of aquaporin-2 (AQP2). Also, estrogen has been known to regulate AQP2. Consistently, we previously demonstrated that tamoxifen (TAM), a selective estrogen receptor modulator, attenuates the downregulation of AQP2 in lithium-induced nephrogenic diabetes insipidus (NDI). In this study, we investigated the AVP-independent regulation of AQP2 by TAM and the therapeutic effect of TAM on the dysregulation of AQP2 and impaired urinary concentration in a unilateral ureteral obstruction (UUO) model. Primary cultured inner medullary collecting duct (IMCD) cells from kidneys of male Sprague-Dawley rats were treated with TAM. Rats subjected to 7 days UUO were treated with TAM by oral gavage. Changes of intracellular trafficking and expression of AQP2 were evaluated by quantitative PCR, western blotting and immunohistochemistry. TAM induced AQP2 protein expression and intracellular trafficking in primary cultured IMCD cells, which were independent of the vasopressin V2 receptor (V2R) and cAMP activation; the critical pathways involved in AVP-stimulated regulation of AQP2. TAM attenuated the downregulation of AQP2 in TGF-β treated IMCD cells and IMCD suspensions pre-pared from UUO rats. TAM administration in vivo attenuated the downregulation of AQP2, associated with an improvement of urinary concentration in UUO rats. In addition, TAM in-creased CaMKII expression, suggesting that calmodulin signaling pathway is likely to be involved in the TAM-mediated AQP2 regulation. In conclusion, TAM is involved in AQP2 regulation in a vasopressin-independent manner and improves urinary concentration by attenuating the down-regulation of AQP2 and maintaining intracellular trafficking in UUO.